A randomized, double-masked study to evaluate the effect of omega-3 fatty acids supplementation in meibomian gland dysfunction - Oleñik A (Dove Medical Press, 2013)
Andrea Oleñik,1 Ignacio Jiménez-Alfaro,1 Nicolás Alejandre-Alba,1 Ignacio Mahillo-Fernández2 1Department of Ophthalmology, Jiménez Díaz Foundation, Madrid, Spain; 2Department of Statistics, Jiménez Díaz Foundation, Madrid, Spain Background: Dysfunction of the meibomian gland (MG) is among the most frequent causes of ophthalmological symptoms. The inflammation seen in meibomian gland dysfunction (MGD) is part of its pathogenesis, and evidence of the antioxidant-inflammatory properties of omega-3 fatty acids suggests this to be an appropriate treatment for MGD. Objective: We aimed to assess the effectiveness of omega-3 fatty acids versus placebo, in improving the symptoms and signs of MGD. Methods: We conducted a randomized and double-mask trial of 3 months duration. We enrolled 61 patients who presented with symptomatic MGD and no tear instability (defined as tear breakup time [TBUT] <10 seconds). Participants were randomly assigned to two homogeneous subgroups. For patients in group A, the study treatment included cleaning the lid margins with neutral baby shampoo and use of artificial tears without preservatives, plus a placebo oral agent. For patients in group B, the study treatment included cleaning the lid margins with neutral baby shampoo and use of artificial tears without preservatives, plus oral supplementation with omega-3 fatty acids. We performed the following tests: (1) TBUT; (2) Schirmer I test; (3) Ocular Surface Disease Index© (OSDI©; Allergan, Inc., Irvine, CA, USA); (4) MG expression; (5) evaluation of lid margin inflammation; and (6) interpalpebral and corneal dye staining. Results: After 3 months of evaluation, the mean OSDI, TBUT, lid margin inflammation, and MG expression presented improvement from the baseline values, in group B (P < 0.01, P < 0.001, P < 0.0001, P < 0.0001, respectively). The Schirmer test results were also improved and statistically significant (P < 0.01). Conclusion: Oral omega-3 fatty acids, 1.5 grams per day, may be beneficial in the treatment of MGD, mainly by improving tear stability. Keywords: blepharitis, dry eye, ocular inflammation, eye discomfort, surface disease